Environmental Governance and International Relations: A Systematic Review of Theories, Methods, and Issues in Latin American Publications - Cia-Alves, Elia Elisa (2023)
Home to the Amazon and other important biomes and to countries with long coastlines, most of Latin America faces a variety of enduring environmental challenges. Nonetheless, the region’s academic production on international environmental policy is fragmented and dispersed. This study aims to systematically analyze the literature on environmental governance in Latin America (2004–2023), with a special focus on theoretical approaches, methods, and issues. Our sample includes papers published in indexed academic journals written in English, Portuguese, or Spanish to answer the following question: How can Latin American literature on environmental policy help us understand environmental governance in the region and globally? Complementarily, we ask the following: What topics have been prioritized? What theories and methods have been used? What gaps remain? We suggest a future research agenda and hope to help strengthen the international relations (IR) environmental governance literature by providing subsidies to improve research in the region.